Factors affecting midwifery students' perceptions of spiritual care: A cross-sectional study of the Eastern Region of Turkey Affecting midwifery students' perceptions of spiritual care - Celebi, Evrim; Can, Hafize Ozturk (Bayrakol Medical Publisher, 2021)
Aim: The aim of this study was to determine the factors affecting midwifery students' perceptions of spiritual care in a particular region. Material and Methods: This descriptive and cross-sectional study included 179 midwifery students. The tools used for data collection were the personal information form and the Turkish version of the Spiritual Care-Giving Scale. Results: Among the students participating in the study, 73.2% had heard of spiritual care. one-third received information about spiritual care, 78.2% did not have enough knowledge about spiritual care, and 17.9% were able to adequately meet the spiritual care needs of the individuals/patients to whom they gave a care. The spiritual care method, which was most commonly used by 82.7% of the participating students, was an empathic approach. According to midwifery students, the most serious barrier to giving spiritual care is the lack of knowledge. The mean score obtained on the Spiritual Care-Giving Scale by the participating midwifery students was 108.50 +/- 12.46. Discussion: The mean scale scores obtained by the students who had previously received information about spiritual care, who wanted to get more information about spiritual care. and who considered that spiritual care was important in midwifery care were found high.
Keywords: Midwifery Student; Midwifery Education; Spirituality; Spiritual